Local hydrophobic glass bead and preparation method thereof

By performing hydrophobic treatment and thermal curing technology on spherical groove substrates, local hydrophobic glass microbeads were prepared, which solved the problem of poor mixing uniformity of glass microbeads in emulsion coatings and resin-based composite materials, and improved the stability of the material and application effects.

CN119143404APending Publication Date: 2024-12-17CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD

Patent Information

Application Number
CN202411119474.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

When glass microbeads are used as emulsion coating fillers or resin-based composite material fillers, the material system has poor mixing uniformity and stability, resulting in poor coating stability and coating effect.

Method used

Local hydrophobic glass microbeads are used, and the surface is equipped with a hydrophobic film layer, accounting for 1/2~4/5 of the surface area. By hydrophobic treatment on the spherical groove substrate, a closed hydrophobic film layer is formed, combining heat treatment and vibration peeling technology. , glass microbeads with both hydrophilicity and hydrophobicity were prepared.

Benefits of technology

Improves the mixing uniformity and bonding force of glass microbeads in the material system, reduces the use of hydrophobic agents and waste liquid generation, is suitable for hollow and solid glass microbeads, avoids dust and organic gas pollution, and improves the stability of the material. and application effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143404A_ABST
    Figure CN119143404A_ABST
Patent Text Reader

Abstract

The invention relates to a locally hydrophobic glass bead and a preparation method thereof, and is characterized in that the preparation method comprises the following steps: (1) selecting a glass bead with D50 of 5-100 [mu] m and a particle size distribution span of not more than 0.2, and cleaning and drying the glass bead; (2) placing glass beads on a substrate provided with a group of spherical grooves; (3) treating the exposed surfaces of the glass beads by using a hydrophobic agent alkyl siloxane or fluorinated siloxane solution, and then carrying out heat treatment to complete curing and film forming; and (4) stripping the glass beads subjected to surface film formation from the substrate provided with the spherical grooves. The invention has the advantages that the glass bead with a hydrophilic and hydrophobic composite surface and the preparation method of the glass bead are provided; the locally hydrophobic glass beads can play a role similar to a surfactant or a coupling agent when being used as an emulsion coating filler or an organic resin-based composite material filler, so that the mixing uniformity of the locally hydrophobic glass beads in a material system is effectively improved, and the binding force is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of glass surface coatings and relates to a partially hydrophobic glass microbead and a preparation method thereof. Background Art

[0002] Glass beads are a micron-sized spherical glass material with a particle size of less than 0.8 mm. They have good sphericity, transparency, hardness, light reflectivity and excellent chemical stability. They can be used as grinding media, polishing materials, catalytic carriers, lightening agents, reflective materials, reinforcing filling materials, etc. They are widely used in machinery, chemical industry, medical treatment, navigation, transportation, oil drilling and other fields. When used as lightening and reinforcing filling materials, glass beads often need to be surface treated to optimize the filling effect.

[0003] For emulsion coatings, when glass beads are used as fillers, if no hydrophobic treatment is performed, the hydrophilic glass beads will mainly gather in the water phase; if the surface of the glass beads is hydrophobic, the hydrophobic glass beads will mainly gather in the oil phase; in both cases, the glass beads cannot be well mixed in the emulsion, thus affecting the stability of the coating and the coating effect. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of poor mixing uniformity and stability of the material system when glass microspheres are used as emulsion coating fillers or resin-based composite material fillers, and to provide a partially hydrophobic glass microsphere and a preparation method thereof.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A partially hydrophobic glass microbead comprises a spherical glass microbead with a closed surface and no pores, characterized in that a hydrophobic film layer is provided on the surface of the glass microbead, wherein the area of ​​the hydrophobic film layer accounts for 1 / 2 to 4 / 5 of the surface area of ​​the glass microbead, the surfaces of the hydrophobic part and the hydrophilic part are respectively continuous, and the contact line of the two surfaces is circular on the surface of the microbead, and the circumference of the circle depends on the proportion of the hydrophobic area.

[0006] A method for preparing locally hydrophobic glass microspheres, characterized by comprising the following steps: (1) Select glass microbeads with a median diameter (D50) ranging from 5 to 100 μm and a particle size distribution span of no more than 0.2, and then wash and dry the glass microbeads for later use; (2) placing the dried glass beads on a substrate with a set of spherical grooves, so that a portion of the surface of the glass beads is exposed. Depending on the size of the selected substrate grooves, the exposed area of ​​the glass beads accounts for 1 / 2 to 4 / 5 of the entire spherical area; (3) The exposed surface of the glass microspheres is treated with a hydrophobic agent (alkyl siloxane or fluorinated siloxane solution), and then heat treated (at 90-200°C for 1-10 min) to complete the curing film formation; (4) The glass microbeads after the surface film is formed are peeled off from the substrate with the spherical grooves to obtain the locally hydrophobic glass microbeads.

[0007] Furthermore, the glass microspheres are solid glass microspheres or hollow glass microspheres. If hollow glass microspheres are used, in order to maintain the structural integrity of the microspheres during the coating process, the compressive strength tested by the air pressure method should meet the following requirements: 20 MPa (10 min), and the ball breakage rate ≤ 20%.

[0008] Furthermore, in the process of obtaining the glass microbeads in step (1), before sorting, the particle size range of the glass microbeads is 1-150 μm; by using a rotary vibrating screen device with sieves of different mesh sizes for sorting, a glass microbead powder meeting the target median diameter and particle size distribution span is obtained.

[0009] Furthermore, the span of the particle size distribution is calculated as (D90-D10) / D50.

[0010] Furthermore, the spherical grooves on the same substrate are arranged equidistantly and are equal in size; the depth of the spherical grooves is less than or equal to the radius of the corresponding sphere; the horizontal spacing of the spherical grooves is between D50 and D97 of the particle size of the glass bead powder, so as to ensure that as many glass beads as possible are arranged in the horizontal direction and reduce excessively large glass beads, so as to facilitate the uniformity and consistency of the glass bead film coating during the scraping process.

[0011] Furthermore, the diameter of the sphere corresponding to the groove is equal to the median diameter (D50) of the glass microbead powder to be hydrophobically treated.

[0012] Furthermore, the substrate is made of rigid materials such as inorganic glass or ceramics.

[0013] Further, the step of treating with a hydrophobic agent is: a. Calculate the approximate number of microbeads that can be placed based on the substrate area and the number of grooves, convert it into the mass of microbead powder, and weigh the glass microbeads of the corresponding mass for later use; b. In order to avoid dust generated by glass microbeads, especially hollow glass microbead powder, in the air, which may cause environmental pollution and waste of raw materials, and to improve the surface treatment efficiency, a vacuum glove box is used to provide an environment for preparing partially hydrophobic glass microbeads; under a negative pressure environment, a certain amount of glass microbeads are dropped at a close distance near one edge of a horizontally placed rectangular substrate through a funnel-shaped discharge port, so that the microbead powder is spread into a strip parallel to the edge of the above substrate, and the length of the strip is equivalent to the side length of the groove array perpendicular to the scraping movement direction; one side of the substrate with the strip is raised and tilted at a certain angle, so that the glass microbeads slide down evenly and slowly into the grooves on the surface of the substrate; or a rubber scraper is used to scrape the glass microbeads spread into the strip on the substrate into the groove array; or the above two methods are combined according to the actual situation such as the size of the microbeads and the area of ​​the substrate; in the process of placing the microbeads into the grooves, the screened glass microbeads with a particle size concentrated near the median diameter remain on the substrate, and a small number of microbeads with too large a particle size roll off or are scraped off the substrate surface; c. Fix the substrate with glass beads on the wire rod coating machine; before coating, drip an appropriate amount of hydrophobic agent along the front of the contact line between the substrate and the wire rod; set the moving speed of the wire rod according to the desired film thickness and the viscosity of the hydrophobic agent to complete the coating process; take the substrate coated with the hydrophobic agent out of the glove box and put it into the heat treatment equipment to solidify the hydrophobic film layer.

[0014] Furthermore, the glass beads peeling method is to separate the hydrophobic glass beads from the substrate by high-frequency vibration; the vibration source includes but is not limited to a pneumatic vibrator, an electric vibrator, and the like.

[0015] Beneficial effects of the present invention: 1. The present invention creatively provides a glass microbead having a composite surface with both hydrophilicity and hydrophobicity and a preparation method thereof; 2. The partially hydrophobic glass microbeads prepared by this method (the local hydrophobicization of the glass microbeads is carried out in batches on a substrate with a spherical groove array. The glass microbeads are hydrophilic before hydrophobization and are solid or hollow structures) have a concentrated particle size distribution and are applicable to both hollow glass microbeads and solid glass microbeads, and are not limited by the density of the glass microbeads; less hydrophobic agent is used, and there is basically no waste liquid and waste of hydrophobic agent; it is prepared in a vacuum glove box, and there is no dust and organic gas pollution; 3. A part of the surface of glass microbeads is hydrophobic, and the rest is hydrophilic. When used as fillers for emulsion coatings or fillers for organic resin-based composite materials, they can play a role similar to that of surfactants or coupling agents, effectively improving their mixing uniformity and bonding strength in the material system. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1The schematic diagram of the substrate structure is provided with a set of 1 / 2 spherical grooves. The horizontal spacing of the spherical grooves is between D50 and D97 of the particle size of the glass microbead powder. Here, the horizontal spacing of the grooves is equal to D50 of the microbead powder. Figure 2 Glass beads and Figure 1 Schematic diagram of substrate bonding shown; Figure 3 The schematic diagram of the substrate structure is provided with a group of grooves smaller than 1 / 2 of the spherical surface. The horizontal spacing of the spherical grooves is between D50 and D97 of the particle size of the glass microbead powder. Here, the horizontal spacing of the grooves is equal to D50 of the microbead powder. Figure 4 Glass beads and Figure 3 Schematic diagram of substrate bonding is shown. DETAILED DESCRIPTION

[0017] The present invention will be further described below in conjunction with the accompanying drawings: A method for preparing locally hydrophobic glass microspheres, the specific implementation steps are as follows: Example

[0018] (1) Use a rotary vibrating screen with sieves of different mesh sizes for sorting, and the median diameter (D50) is 50 μm, the particle size distribution span is no more than 0.08 (the particle size distribution span is calculated as (D90-D10) / D50), and the true density is 0.50 g / cm 3 The hollow glass microspheres are cleaned and dried for later use; (2) Based on a borosilicate glass substrate with a size of 340 mm × 340 mm × 4 mm, a set of 1 / 2 spherical grooves (such as Figure 1 ), the diameter of the sphere corresponding to the groove is equal to 50μm, and the horizontal size of the groove array is 300mm×300mm; (3) Applying the alkylsiloxane solution to the exposed hollow glass microsphere surface by a scraping process: Weigh 1.18 g of glass microspheres for later use; Using a vacuum glove box to provide an environment for preparing locally hydrophobic glass microspheres, under a negative pressure environment, drop the prepared glass microspheres through a funnel-shaped discharge port at a close distance to one edge of a horizontally placed rectangular substrate, so that the microsphere powder is spread into a strip parallel to the edge of the substrate, and the length of the strip is equivalent to the side length of the groove array perpendicular to the scraping movement direction; Raise one side of the substrate with the strip (tilted 3°), so that the glass beads slide down evenly and slowly into the grooves on the surface of the substrate; in the process of placing the beads into the grooves, the screened glass beads with a particle size concentrated near the median diameter remain on the substrate, and 1 / 2 of the surface of the glass beads is exposed (such as Figure 2), a small number of beads with too large particle size rolled off or were scraped off the surface of the substrate; the substrate with glass beads placed was fixed on the wire rod scraper; before scraping, a hydrophobic agent was dripped along the front of the contact line between the substrate and the wire rod, and the moving speed of the wire rod during the scraping process was controlled to be 2 cm / s. The substrate coated with the hydrophobic agent was taken out of the glove box and placed in a heat treatment equipment for heat treatment, and the film was cured at 120℃ for 5 minutes; (4) The substrate is then fixed on an inclined slot (inclined at an angle of 30°) with the side containing the hollow glass microbeads facing outward. A pneumatic vibrator is mounted on the back of the slot. The vibrator is turned on for 20 seconds to separate the hydrophobic glass microbeads from the substrate by vibration, thereby obtaining a partially hydrophobic glass microbead. (5) Clean the used substrates for recycling. Example

[0019] (1) Use a rotary vibrating screen with sieves of different mesh sizes for sorting, and the median diameter (D50) is 10 μm, the particle size distribution span is no more than 0.2 (the particle size distribution span is calculated as (D90-D10) / D50), and the true density is 2.50 g / cm 3 Solid glass microbeads are washed and dried for later use; (2) Based on an alumina ceramic substrate with a size of 340 mm × 340 mm × 4 mm, a set of 1 / 2 spherical grooves (such as Figure 1 ), the diameter of the sphere corresponding to the groove is equal to 10μm, and the horizontal size of the groove array is 300mm×300mm; (3) Coating the fluorinated siloxane solution on the exposed surface of the hollow glass microspheres by a scraping process: Weigh 1.18 g of glass microspheres for later use; Use a vacuum glove box to provide an environment for preparing locally hydrophobic glass microspheres. Under a negative pressure environment, drop the prepared glass microspheres through a funnel-shaped discharge port at a close distance near one of the edges of a horizontally placed rectangular substrate, so that the microsphere powder is spread into a strip parallel to the edge of the substrate, and the length of the strip is equivalent to the side length of the groove array perpendicular to the scraping movement direction; Raise one side of the substrate covered with the strip (tilted 3°) to allow the glass microspheres to slide down evenly and slowly into the grooves on the surface of the substrate; In the process of placing the microspheres into the grooves, the screened glass microspheres with a particle size concentrated near the median diameter remain on the substrate (such as Figure 2 ), a small number of beads with too large particle size rolled off or were scraped off the surface of the substrate; the substrate with glass beads placed was fixed on the wire rod scraper; before scraping, a hydrophobic agent was dripped along the front of the contact line between the substrate and the wire rod, and the moving speed of the wire rod during the scraping process was controlled to be 1 cm / s. The substrate coated with the hydrophobic agent was taken out of the glove box and placed in a heat treatment equipment for heat treatment, and the film was cured at 150°C for 5 minutes; (4) The substrate is then fixed on an inclined slot (inclined at an angle of 45°) with the side containing the solid glass beads facing outward. A pneumatic vibrator is mounted on the back of the slot. The vibrator is turned on for 40 seconds to separate the hydrophobic solid glass beads from the substrate by vibration, thereby obtaining a partially hydrophobic glass bead. (5) Clean the used substrates for recycling. Example

[0020] (1) Using a rotary vibrating screen with sieves of different mesh sizes for sorting, the median diameter (D50) is 30 μm, the particle size distribution span is no more than 0.1 (the particle size distribution span is calculated as (D90-D10) / D50), and the true density is 0.55 g / cm 3 The hollow glass microspheres are cleaned and dried for later use; (2) Based on a borosilicate glass substrate with a size of 340 mm × 340 mm × 4 mm, a set of spherical grooves with a depth of 7.50 μm were custom-processed on one surface (e.g. Figure 3 ), the diameter of the sphere corresponding to the groove is equal to 30μm, and the horizontal size of the groove array is 300mm×300mm; (3) Applying the alkylsiloxane solution to the exposed hollow glass microsphere surface by a scraping process: Weigh 0.78 g of glass microspheres for later use; Using a vacuum glove box to provide an environment for preparing locally hydrophobic glass microspheres, under a negative pressure environment, drop the prepared glass microspheres through a funnel-shaped discharge port at a close distance near one edge of a horizontally placed rectangular substrate, so that the microsphere powder is spread into a strip parallel to the edge of the substrate, and the length of the strip is equivalent to the side length of the groove array perpendicular to the scraping movement direction; Using a rubber scraper, scrape the glass microspheres spread into the strip on the substrate and drop them into the groove array; In the process of placing the microspheres into the grooves, the screened glass microspheres with a particle size concentrated near the median diameter remain on the substrate (such as Figure 4 ), a small number of beads with too large particle size rolled off or were scraped off the surface of the substrate; the substrate with glass beads placed was fixed on the wire rod scraper; before scraping, a hydrophobic agent was dripped along the front of the contact line between the substrate and the wire rod, and the moving speed of the wire rod during the scraping process was controlled to be 2.5 cm / s. The substrate coated with the hydrophobic agent was taken out of the glove box and placed in a heat treatment equipment for heat treatment, and the film was cured at 120°C for 8 minutes; (4) The substrate is then fixed on an inclined slot (inclined at an angle of 40°) with the side containing the hollow glass microbeads facing outwards. An electric vibrator is attached to the back of the slot. The vibrator is turned on for 30 seconds to separate the hydrophobic glass microbeads from the substrate by vibration, thereby obtaining a partially hydrophobic glass microbead. (5) Clean the used substrates for recycling. Example

[0021] (1) The median diameter (D50) of the particles was 75 μm and the particle size distribution span was no more than 0.2 (the particle size distribution span was calculated as (D90-D10) / D50). The true density was 0.38 g / cm 3 The hollow glass microspheres are cleaned and dried for later use; (2) Based on a quartz glass substrate with a size of 340 mm × 340 mm × 4 mm, a set of spherical grooves with a depth of 18.75 μm were custom-processed on one surface (e.g. Figure 3 ), the diameter of the sphere corresponding to the groove is equal to 75μm, and the horizontal size of the groove array is 300mm×300mm; (3) Applying the alkylsiloxane solution to the exposed hollow glass microsphere surface by scraping: Weigh 1.35 g of glass microspheres for later use; Using a vacuum glove box to provide an environment for preparing locally hydrophobic glass microspheres, under a negative pressure environment, drop the prepared glass microspheres through a funnel-shaped discharge port at a close distance near one of the edges of a horizontally placed rectangular substrate, so that the microsphere powder is spread into a strip parallel to the edge of the substrate, and the length of the strip is equivalent to the side length of the groove array perpendicular to the scraping movement direction; Raise one side of the substrate with the strip (tilted 5°) to allow the glass microspheres to slide down evenly and slowly into the grooves on the surface of the substrate; At the same time, use a rubber scraper to scrape the glass microspheres spread into the strip on the substrate into the groove array; In the process of placing the microspheres into the grooves, the screened glass microspheres with a particle size concentrated near the median diameter remain on the substrate (such as Figure 4 ), a small number of beads with too large particle size rolled off or were scraped off the surface of the substrate; the substrate with glass beads placed was fixed on the wire rod scraper; before scraping, a hydrophobic agent was dripped along the front of the contact line between the substrate and the wire rod, and the moving speed of the wire rod during the scraping process was controlled to be 4 cm / s. The substrate coated with the hydrophobic agent was taken out of the glove box and placed in a heat treatment equipment for heat treatment, and the film was cured at 150°C for 5 minutes; (4) The substrate is then fixed on an inclined slot (inclined at an angle of 25°) with the side containing the hollow glass microbeads facing outwards. An electric vibrator is attached to the back of the slot. The vibrator is turned on for 20 seconds to separate the hydrophobic glass microbeads from the substrate by vibration, thereby obtaining a partially hydrophobic glass microbead. (5) Clean the used substrates for recycling.

Claims

1. A partially hydrophobic glass microsphere, comprising a spherical glass microsphere with a closed surface and no pores, characterized in that: A hydrophobic film layer is provided on the surface of the glass microbead, wherein the area of ​​the hydrophobic film layer accounts for 1 / 2 to 4 / 5 of the surface area of ​​the glass microbead. The surfaces of the hydrophobic part and the hydrophilic part are respectively continuous, and the contact line of the two surfaces is circular on the surface of the microbead.

2. A method for preparing locally hydrophobic glass microspheres, characterized in that The steps include: (1) Select glass microbeads with a median diameter range of 5 to 100 μm and a particle size distribution span of no more than 0.2, and then wash and dry the glass microbeads for later use; (2) placing the dried glass beads on a substrate having a set of spherical grooves, so that a portion of the surface of the glass beads is exposed, and the exposed area of ​​the glass beads accounts for 1 / 2 to 4 / 5 of the entire spherical area; (3) The exposed surface of the glass microspheres is treated with a hydrophobic agent alkyl siloxane or fluorinated siloxane solution, and then cured to form a film through heat treatment; (4) The glass microbeads after the surface film is formed are peeled off from the substrate with the spherical grooves to obtain the locally hydrophobic glass microbeads.

3. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that: The glass microspheres are solid glass microspheres or hollow glass microspheres whose compressive strength satisfies that the breakage rate is not greater than 20% under an air pressure of 20 MPa.

4. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that: The spherical grooves on the same substrate are arranged equidistantly and are equal in size; the depth of the spherical grooves is less than or equal to the radius of the corresponding sphere; and the horizontal spacing of the spherical grooves is between D50 and D97 of the particle size of the glass microbead powder.

5. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that: The diameter of the sphere corresponding to the groove is equal to the median diameter of the glass microbead powder to be treated with hydrophobicity.

6. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that The substrate is made of inorganic glass or ceramic.

7. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that: The heat treatment temperature is 90-200° C. and the time is 1-10 min.

8. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that The steps of using a hydrophobic agent for treatment are: a. A vacuum glove box is used to provide an environment for preparing partially hydrophobic glass microbeads. Under a negative pressure environment, the glass microbeads are dropped at a close distance near one edge of a horizontally placed rectangular substrate through a funnel-shaped discharge port, so that the microbead powder is spread into a strip parallel to the edge of the substrate, and the length of the strip is equivalent to the side length of the groove array perpendicular to the coating movement direction; one side of the substrate with the strip is raised and tilted at a certain angle, so that the glass microbeads slide down evenly and slowly into the grooves on the surface of the substrate; or a rubber scraper is used to scrape the glass microbeads spread into the strip on the substrate into the groove array; or the above two methods are combined according to the actual situation such as the size of the microbeads and the area of ​​the substrate; in the process of placing the microbeads into the grooves, the screened glass microbeads with a particle size concentrated near the median diameter remain on the substrate, and a small number of microbeads with a particle size that is too large roll off or are scraped off the substrate surface; b. Fix the substrate with glass beads on the wire rod coating machine; before coating, drip the hydrophobic agent along the front of the contact line between the substrate and the wire rod; set the moving speed of the wire rod to complete the coating process; take the substrate coated with the hydrophobic agent out of the glove box and put it into the heat treatment equipment to solidify the hydrophobic film layer.

9. The method for preparing partially hydrophobic glass microspheres according to claim 2, characterized in that: The glass microbead peeling method is to separate the hydrophobic glass microbead from the substrate by high-frequency vibration.

10. The method for preparing partially hydrophobic glass microspheres according to claim 9, characterized in that Vibration sources include, but are not limited to, pneumatic vibrators and electric vibrators.

Citation Information

Patent Citations

  • Solder strip reflection assembly, reflection solder strip and photovoltaic battery assembly, and preparation method thereof

    CN108242476A

  • Outer barrier wall structure

    CN111691573A

  • Product in which the surface of the particles is partly hydrophilic and partly hydrophobic

    WO1989008621A1

Cited By

  • Preparation method of surface modified hollow glass beads

    CN119954401A

  • A method for preparing surface-modified hollow glass microspheres

    CN119954401B